MEDIA AND FRAGMENTATION OF RELIGIOUS AUTHORITIES (Social Media and the Shift of Religious Authority in the Post truth Era) - Sabaruddin S; Muya Syaroh Iwanda Lubis; Mailin Mailin (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2021)
AbstractThe era of new media affects fundamental changes in all aspects of human life as well as being a human need, both individually and in social relations, and fundamental changes in the social, political, economic, and cultural fields. Moreover, there are fundamental changes in aspects of religious thought, fatwas, and practice, as well as the relationships established on the basis of religious norms. Following the observations of Teusner and Cambell, this trend is both a challenge and a hope for religions. The use of modern technology and media has opened the door to new and creative thinking about how to organize and plan a political movement and social revolution that is rapidly gaining global influence. Very important changes in the religious aspect, among others, are the shift in religious authority and the patterns of relationships between followers and religious figures or leaders who become role models in everyday life. So far, religious authority only belongs to the ulama, murshid, religious teachers or ustad. Religious authority is also in the strong grip of the government through the ministry of religious affairs and non-governmental institutions such as religious mass organizations (ormas). So that religious control is also held by related parties who have full power. So don't be surprised if the influence of social media makes a shift in religious authority in the Post Truth Era which is increasingly rampant. Keywords: Media, Fragmentation, Authority